Proton enhanced dynamic battery chemistry for aprotic lithium–oxygen batteries - Yun Guang Zhu (Nature Portfolio, 2017)
Water is believed to undermine the performance of aprotic lithium–air batteries. However, the authors here disclose different battery chemistry, showing that both lithium ions and protons are involved in the battery reactions in the presence of water, leading to an unprecedented dynamic product.